Health Benefits Due to Reduction in Respirable Particulates during COVID-19 Lockdown in India - Anubha Goel; Pallavi Saxena; Saurabh Sonwani; Shubham Rathi; Ananya Srivastava; Akash Kumar Bharti; Supreme Jain; Shubhanshi Singh; Anuradha Shukla; Anju Srivastava (Aerosol and Air Quality Research)
Abstract To control the spread of the coronavirus (COVID-19) pandemic, the Government of India imposed various phases of lockdown starting from the third week of March 2020. Improvement in city air quality has emerged as a benefit of this lockdown in India. The objective of this paper is to quantify the health benefits due to this lockdown. PM2.5 concentrations in nonattainment cities (NACs) in Uttar Pradesh and the Delhi-National Capital Region (NCR) in North India were studied. Data from prelockdown and the various lockdown phases were compared, with 2019 as a benchmark. Compared with those in 2019, the PM2.5 concentrations during lockdown Phase 1 were approximately 44.6% lower for cities in Uttar Pradesh and approximately 58.5% lower for the Delhi-NCR. The health impacts of particle inhalation were quantified using the multiple-path particle dosimetry and AirQ+ models, which revealed that the most considerable improvement was during lockdown Phase 1. Among the prelockdown and lockdown phases, Phase 1 exhibited the minimum PM2.5 concentration and thus the greatest health benefits. For the selected cities, the concentration of particle deposition in the tracheobronchial region of human lungs showed its maximum reduction during lockdown Phase 1(30.14%). Furthermore, the results highlighted a decrease of 29.85 deaths per 100,000 persons during lockdown Phase 1, primarily due to the reduction in PM2.5 concentrations. This quantification of the health benefits due to a decrease in PM2.5 may help policymakers implement suitable control measures, especially for NACs, where the respirable particulate matter concentrations remain very high.